The Effect of Extremely Low‐Frequency Electromagnetic Fields on the Prevalence of Musculoskeletal Disorders and the Role of Oxidative Stress. Issue 5 (18th June 2019) - Hosseinabadi, Majid Bagheri; Khanjani, Narges
Abstract : Extremely low‐frequency electromagnetic fields (ELF‐EMFs) may cause negative health effects. This study aimed to investigate the direct and indirect effects of chronic exposure to extremely low‐frequency electric and magnetic fields on the prevalence of musculoskeletal disorders (MSDs). In this cross‐sectional study, 152 power plant workers were enrolled. The exposure level of employees was measured based on the IEEE Std C95.3.1 standard. Superoxide dismutase (SOD), catalase (Cat), glutathione peroxidase (GPx), total antioxidant capacity (TAC), and malondialdehyde (MDA) (independent variables) were measured in the serum of subjects. The Nordic musculoskeletal questionnaire was used to assess MSDs (dependent variable). The mean exposure of electric and magnetic fields were 4.09 V/m (standard deviation [SD] = 4.08) and 16.27 µT (SD = 22.99), respectively. Increased levels of SOD, Cat, GPx, and MDA had a direct significant relation with MSDs. In the logistic regression model, SOD (odds ratio [OR] = 0.952, P = 0.026), GPx (OR = 0.991, P = 0.048), and MDA (OR = 0.741, P = 0.021) were significant predictors of MSDs. ELF‐EMFs were not related to MSDs directly; however, increased levels of oxidative stress may cause MSDs. Bioelectromagnetics. 2019;40:354–360. © 2019 Bioelectromagnetics Society.